Re-voicing the unheard: Meta-study on arts-based interventions for social inclusion of refugees and asylum-seekers - Alves Moreira, Ana I.; Jakobi, Antonia L. P. (Journal of Education Culture and Society, 2021)
Aim. This study aims to explore and analyse qualitative research on refugee and asylum-seeker interventions for social inclusion that engages a creative, arts-based community approach. Method. The article describes a meta-study towards discovering meta-theory, meta-methods, and meta-findings across articles on the subject. For this purpose, a broad database search was conducted, which resulted in a total of 7 articles after filtering according to the previously defined exclusion criteria. These articles were analysed by two independent researchers and later reviewed by two independent evaluators. Results and conclusion. There was an overarching lack of definitions and distinction of and for the terms refugee, migrant and asylum-seeker. A similar problem could also be found regarding social inclusion and integration which were, at times, used interchangeably. Additionally, the majority of the studies opted for an ethnographic approach despite choosing different methods within the said approach. Concerning the meta findings, three main themes emerged across research: space of expression and confidence; transformation process to agency and citizenship; and exchange and dialogue between the host community and arrivals. These themes were discussed and reflected upon, and limitations were pointed out. Originality. Having identified the lack of refugee and asylum-seeker voices within migration studies, this article sets out to counteract this issue by having included only those articles that provided space for refugee and asylum-seeking individuals to speak up, thereby authentically understanding arts-based social inclusion interventions from a new and neglected angle.